Probiotic supplementation in sports and physical exercise: Does it present any ergogenic effect?. Issue 4 (December 2017) - Coqueiro, Audrey Yule; de Oliveira Garcia, Amanda Beatriz; Rogero, Marcelo Macedo; Tirapegui, Julio
Background: Probiotics are live microorganisms that promote health benefits to the host. Evidence indicates that some probiotic strains play an immunomodulatory role and reduce the incidence of respiratory and gastrointestinal infections in athletes and in physical activity practitioners. For this reason, probiotic supplementation could indirectly improve exercise performance. However, recent studies have observed direct ergogenic effects of probiotics, but the mechanisms of action are poorly elucidated. Objective: In this study, we aim to synthesize available knowledge on the effect of probiotics on physical exercise, identify the mechanisms of action by which probiotics could improve performance directly and indirectly, and verify whether probiotics have any ergogenic effect. Methods: The study was performed in the PubMed database in February 2017, without limitation as to the publication period. The keyword combinations used were: 'Probiotics' and 'Sports' ( n = 17 articles), 'Probiotics' and 'Exercise' ( n = 26 articles) and 'Probiotics' and 'Athletes' ( n = 11 articles). Results: Of the 16 studies evaluated, only six applied performance tests, of which only two demonstrated that probiotic supplementation increases performance, but one of them was performed with mice. Conclusions: According to the studies evaluated, probiotic supplementation does not present ergogenic effect, however, considering the small number of studies, this subject should be better investigated.